Enhancement of Bacterial Anti-Adhesion Properties on Robust PDMS Micro-Structure Using a Simple Flame Treatment Method - Nongluck Houngkamhang; Ploymanee Chaisawat; Waisaree Joksathit; Sutichai Samart; Sutee Chutipaijit; Suphichaya Radomyos; Pawasuth Saengdee; Nithi Atthi (Nanomaterials, 2022)
adhesion on the C-RESS-F micro-pattern with hydrophobicity and superoleophobicity was 42.6%, 31.8%, and 2.9% less than FLT-F, PIL-F, and Teflon surfaces. Therefore, the flame-treated C-RESS-F pattern is one of the promising bacterial anti-adhesion micro-structures in practical utilization for various applications.
Keywords: Polymer Surface Interaction Studies; Marine Biology and Environmental Chemistry; Nanofabrication and Lithography Techniques